Pengaruh Modal Intelektual terhadap Kinerja Bisnis UMKM Bidang Kreatif - Febthian Lindenn Harahap; Hariyati Hariyati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Intellectual capital represents information that reflects the quality of human resources and the knowledge assets owned by a business unit. This study aims to examine the influence of intellectual capital on business performance in creative sector MSMEs, specifically in the fashion and beauty industries in Surabaya. Data were collected through questionnaires distributed to business owners to capture their understanding of the components of intellectual capital and its impact on business performance. The study employs a quantitative method with a correlational approach to analyze the relationships between variables. The results of significance tests indicate that intellectual capital overall has a notable impact on business performance. Specifically, Human Capital, Structural Capital, Relational Capital, Technological Capital, and Business Capital exert a positive influence, demonstrating that the quality of human resources, organizational structure, business relationships, technology utilization, and business assets are key factors in improving MSME performance. Conversely, Customer Capital shows a negative influence, highlighting the need for more effective strategies in managing and leveraging customer-related resources. These findings confirm that intellectual capital significantly affects the performance of creative sector MSMEs, suggesting that proper management and development of each component of intellectual capital is essential for enhancing competitiveness, sustaining growth, and ensuring the long-term success of small and medium enterprises.